To dine in or not to dine in: A comparison of food selection and preparation behaviours in those with and without food security. (20th October 2020) - Butcher, Lucy M.; O'Sullivan, Therese A.; Ryan, Maria M.; Lo, Johnny; Nyanjom, Julie; Wilkins, Hugh C.; Devine, Amanda
Abstract: Issue addressed: Vulnerable populations are disproportionately affected by food insecurity, resulting in heightened risk of suboptimal dietary intake. Food insecure people appear to implement several coping strategies and dietary compromises to avoid hunger. Less explored in the literature is how these strategies impact consumption of food inside and outside of the home. Methods: An online survey was completed by adults (n = 1292) residing in one of five Australian states. The questionnaire comprised of the six‐item US Household Food Security Survey Module, 12 socio‐demographic variables and 32 questions related to elements of food literacy. Results: Food insecure respondents were more likely to frequent fast food vs ( P = .002), takeaway ( P < .001) and food courts ( P < .001) than their food secure counterparts. Food secure respondents reported greater use of raw ( P = .043) and fresh, pre‐prepared produce ( P = .002) when cooking, whereas food insecure respondents were more likely to prepare food using only frozen, pre‐packaged products ( P < .001). No significant differences were found between food security status and the enjoyment and social bonding derived from cooking. Conclusions: Food insecure respondents appeared to be accessing a poorer quality of food through greater consumption of takeaway and fast food. These dietary compromises are most likely related to perceived financial, time or cooking facility constraints and to a lesser extent food literacy skills. So what?: This study highlights some of the health and social inequities apparent within food insecure populations. Food insecure households should be supported to access healthy fresh food and in‐home cooking practices. While a multi strategy approach is required, healthy food environment policy, particularly in disadvantaged areas, should be considered to guarantee that all Australians have dignified access to nutritious food.